2020
DOI: 10.20473/j.djmkg.v53.i1.p30-35
|View full text |Cite
|
Sign up to set email alerts
|

Correlation of the vertical dimension of occlusion with five distances between facial landmarks among those of Batak Toba ethnicity

Abstract: Background: The normal vertical dimension of occlusion (VDO) results in orofacial and temporomandibular joint (TMJ) biomechanical balance. If the VDO changes due to attrition, full edentulism, accidents involving the lower third of the face and even improper denture manufacturing will result in the disruption of mastication, speech and aesthetic functions. Therefore, the right technique is needed to predict the correct VDO. Purpose: To identify the correlation values and regression equation of the VDO for five… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 10 publications
1
1
0
Order By: Relevance
“…Similar results were reported 26 , 2D has strong correlation in males, the mean length being 71.6 mm while length of little finger (5D) has a strong correlation in females both having teeth present, the length of the little finger does not match with the current study. One study concluded the mean OVD for males being 70.76 mm similar to that of the current study which is 69.73 mm, and for females 64.54 mm in contrast to the current study’s female population because of apparent anthropometric variations in race and ethnicity 25 . A significant correlation between the length of each of these fingers (2D, 4D and 5D) and the OVD measured from distances Sn–Me as well as N–Gn.…”
Section: Discussionsupporting
confidence: 73%
See 1 more Smart Citation
“…Similar results were reported 26 , 2D has strong correlation in males, the mean length being 71.6 mm while length of little finger (5D) has a strong correlation in females both having teeth present, the length of the little finger does not match with the current study. One study concluded the mean OVD for males being 70.76 mm similar to that of the current study which is 69.73 mm, and for females 64.54 mm in contrast to the current study’s female population because of apparent anthropometric variations in race and ethnicity 25 . A significant correlation between the length of each of these fingers (2D, 4D and 5D) and the OVD measured from distances Sn–Me as well as N–Gn.…”
Section: Discussionsupporting
confidence: 73%
“…A similar study on dentate Sudanese women, indicated correlations between different finger lengths, namely the index finger (2D), the ring finger (4D) and little finger (5D) with the OVD 24 . There have been established studies on dentate individuals that the length of index finger (2D) has strong correlation with the OVD in males while length of little finger (5D) has strong correlation with the OVD in females in different populations 25 27 . The length of the thumb can be fundamentally correlated for OVD measurements when compared with the distance from rima oris to pupil of the eye 28 , as well as the eye-ear distance and pupil of the eye to rima oris 29 .…”
Section: Introductionmentioning
confidence: 99%